Calculation by UFF method of frequencies and vibrational temperatures of the unit cell of the rhodochrosite crystal - Gobato, Ricardo; Regina Risso Gobato, Marcia; Heidari, Alireza (International Journal of Advanced Chemistry, 2019)
The electronic oscillator circuit that uses the mechanical resonance of a vibrating crystal of piezoelectric material to create an electrical signal with a precise frequency is a crystal oscillator. Particularly one using a quartz crystal works by distorting the crystal with an electric field, when voltage is applied to an electrode near or on the crystal. Other crystals such as rhodochrosite also have piezoelectric properties. The rhodochrosite as crystal oscillator for being an alternative to those of quartz. The rhodochrosite (MnC03) shows complete solid solution with siderite (FeC03), and it may contain substantial amounts of Zn, Mg, Co, and Ca. A molecular dynamic via molecular mechanics using the UFF (Universal Forces Field) provided the vibrational frequencies of the fundamental structure of the crystal molecule. The frequencies and vibrational temperatures of the unit cell of rhodochrosite obtained by UFF were calculated in the range from 0.6059 to 1,731.38 cm-1 and 0.87 to 2,491.06 K, respectively.Â Â
Keywords: Rhodochrosite; UFF; Synchrotron Radiation; Quartz Crystal; RLC Circuit; Cancer Cells.